Peptide Epitope-Based Avian IgY Antibodies against SARS-CoV-2 Spike: A Cost Effective Approach for Viral Detection and Neutralization - G. N. Pramod; Prasan Havlad; Nalina Murthy; Abdul Majid; Jessie Thomas; M. Ghalib Enayathullah; Yogesh Sardana; P. K. Sreeram; S. P. Muthukumar; Tanaji Kudre; Pananghat Gayathri; Kiran Kumar Bokara; et al. (International Journal of Peptide Research and Therapeutics, 2025)

Retraction Note: Structural characterization of Bacillus licheniformis Dahb1 exopolysaccharide—antimicrobial potential and larvicidal activity on malaria and Zika virus mosquito vectors - Muthukumar Abinaya; Baskaralingam Vaseeharan; Mani Divya; Sekar Vijayakumar; Marimuthu Govindarajan; Naiyf S. Alharbi; Jamal M. Khaled; Mohammed N. Al-anbr; Giovanni Benelli (Environmental Science and Pollution Research, 2025)

Recurrent Swarms of Planktonic Shrimp Luciferidae De Haan, 1849 (Order: Decapoda) in the Neritic Waters of Tamil Nadu, Southeast Coast of India - R. S. Sathishkumar; B. Charan Kumar; C. Muthukumar; N. Logesh; Sanitha K. Sivadas; K. Ramu; M. V. Ramana Murthy (Marine Ecology, 2024)
Luciferidae (Decapoda) are an important component of mesozooplankton in pelagic food webs. This study investigated the spatiotemporal distribution and frequency of Luciferidae swarms along the Tamil Nadu coast, as observed during coastal monitoring cruises conducted between 2019 and 2022. Data were collected on various hydrobiological factors, including surface water temperature, salinity, chlorophyll a , zooplankton biomass, and the abundance of other mesozooplankton (such as copepods, cladocerans, and others) across eight locations in the coastal waters of Tamil Nadu, India. Salinity values were generally low ( Belzebub hanseni Nobili, 1905, as the only organism responsible for swarm formation, with its occurrence peaking in January 2022. During this period, B. hanseni reached a maximum abundance of 3294 ind. m −3 for adults and 4056 ind. m −3 for larvae, together contributing approximately 27% of the total zooplankton abundance. Swarms of B. hanseni were observed a total of seven times over the course of the study, correlating with periods of low sea surface temperature and high food availability. Pearson's correlation analysis revealed a significant relationship between the abundance of copepods and B. hanseni ( r = 0.84; p B. hanseni in the nearshore waters of the Tamil Nadu coast is largely driven by food availability and optimal environmental conditions, including water temperature and monsoonal influences. The findings also suggest that geographical features, such as mangrove habitats, may contribute to the occurrence of B. hanseni swarms in this region.

An absorber of parabolic trough collector for hydrogen production in a solid oxide fuel cell - T. Sathish; C. Sailaja; R. Saravanan; Pelluru Suresh; M. Anish; M. Rajasimman; Usha Sambath; N. Sabarirajan; K. Muthukumar; Sang-Woo Joo; Yasser Vasseghian (Fuel, 2023)

Thermal performance and emission analysis of self-aspirated kerosene pressure stove with porous radiant burner using kerosene nanofuels - G. S. Sinha; N. Kumar Mishra; P. Muthukumar; M. Sharma (International Journal of Environmental Science and Technology, 2023)

Strain Identification and Herbivore–Host Interaction of Maize Hosting Invasive Alien Pest Spodoptera frugiperda under Elevated Temperature and CO2 Levels - K. Ashok; V. Balasubramani; M. Muthukumar; J. S. Kennedy; V. Geethalakshmi; N. Sathiah (Agricultural Research, 2023)

Photocatalytic degradation of caffeine and E. coli inactivation using silver oxide nanoparticles obtained by a facile green co-reduction method - Harshiny Muthukumar; Santosh Kumar Palanirajan; Manoj Kumar Shanmugam; Pugazhendhi Arivalagan; Sathyanarayana N. Gummadi (Clean Technologies and Environmental Policy, 2022)

Sustenance of Indian Moored Buoy Network During COVID-19 Pandemic – A Saga of Perseverance - R. Venkatesan; K. Jossia Joseph; C. Anoopa Prasad; M. Kalyani; M. Arul Muthiah; S. Ramasundaram; P. Murugesh; K. Thirumurugan; R. Sundar; B. Kesavakumar; G. Vengatesan; K. Ramesh; et al. (Frontiers in Marine Science, 2021)
The moored buoy network in the Indian Ocean revolutionized the observational programs with systematic time-series measurement of in situ data sets from remote marine locations. The real-time meteorological and oceanographic data sets significantly improved the weather forecast and warning services particularly during extreme events since its inception in 1997. The sustenance of the network requires persistent efforts to overcome the multitude of challenges such as vandalism, biofouling, rough weather, corrosion, ship time availability, and telemetry issues, among others. Besides these, the COVID-19 pandemic constrained the normal functioning of activities, mainly by delaying the maintenance of the network that resulted in losing a few expensive buoy system components and precious data sets. However, the improvements in the buoy system, in-house developed data acquisition system, and efforts in ensuring the quality of measurements together with “best practice methods” enabled 73% of the buoy network to be functional even when the cruises were reduced to 33% during the COVID-19 lockdown in 2020. The moored buoys equipped with an Indian buoy data acquisition system triggered high-frequency transmission during the Super cyclone Amphan in May 2020, which greatly helped the cyclone early warning services during the COVID-19 pandemic. The COVID-19 lockdown points toward the reliability and enhanced utility of moored buoy observations particularly when other modes of measurements are limited and necessitates more such platforms to better predict the weather systems. The present study analyzed the enhancement of the buoy program and improvisation of the buoy system that extended the life beyond the stipulated duration and enabled the high-frequency data transmission during cyclones amid the COVID-19 lockdown. The recommendations to better manage the remote platforms specifically in the event of a pandemic based on the operational experience of more than two decades were also presented.

RETRACTED ARTICLE: Structural characterization of Bacillus licheniformis Dahb1 exopolysaccharide—antimicrobial potential and larvicidal activity on malaria and Zika virus mosquito vectors - Muthukumar Abinaya; Baskaralingam Vaseeharan; Mani Divya; Sekar Vijayakumar; Marimuthu Govindarajan; Naiyf S. Alharbi; Jamal M. Khaled; Mohammed N. Al-anbr; Giovanni Benelli (Environmental Science and Pollution Research, 2018)

Developmental stages and secondary compound biosynthesis of mycobiont and whole thallus cultures of Buellia subsororioides - Karthik Shanmugam; Muthukumar Srinivasan; G. N. Hariharan (Mycological Progress, 2016)

Introgression of bacterial leaf blight resistance and aroma genes using functional marker-assisted selection in rice (Oryza sativa L.) - R. K. Salgotra; B. B. Gupta; Reginald J. Millwood; Muthukumar Balasubramaniam; C. N. Stewart (Euphytica, 2012)

Optimization of Antimicrobial Production by a Marine Actinomycete Streptomyces afghaniensis VPTS3-1 Isolated from Palk Strait, East Coast of India - R. Vijayakumar; K. Panneerselvam; C. Muthukumar; N. Thajuddin; A. Panneerselvam; R. Saravanamuthu (Indian Journal of Microbiology, 2012)

Biodegradation of palmarosa oil (green oil) by Serratia marcescens - S. Mohanan; S. Maruthamuthu; N. Muthukumar; A. Rajasekar; N. Palaniswamy (International Journal of Environmental Science and Technology, 2007)

Microbiologically influenced corrosion in dairy effluent - B. Ramesh Babu; S. Maruthamuthu; A. Rajasekar; N. Muthukumar; N. Palaniswamy (International Journal of Environmental Science and Technology, 2006)